2020
DOI: 10.1002/erv.2805
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic vulnerability factors in eating disorders: A network analysis

Abstract: Objective: Eating disorder (ED) symptoms and transdiagnostic vulnerability characteristics play a crucial role in the aetiology and maintenance of EDs. Over the last decade, researchers have started to model complex interrelations between symptoms using network models, but the literature is limited in that it has focused solely on symptoms and investigated-specific disorders while ignoring transdiagnostic aspects of mental health. Method: This study tackles these challenges by investigating network relations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 91 publications
(112 reference statements)
3
48
0
1
Order By: Relevance
“…Moreover, ineffectiveness and interoceptive awareness were identified in the shortest pathway between emotional abuse and drive to thinness or bulimic symptoms in people with AN restricting type and with AN purging type or BN, respectively. In accordance with this study, early maladaptive schema (over‐vigilance and inhibition of emotions and impaired autonomy and performance) were external field nodes resulting highly central in samples with mixed EDs (Vervaet et al., 2020), although their possible bridge role was not assessed. Another study (Monteleone, Corsi, et al., 2020) explored the connections of ED‐specific and affective symptoms with mentalizing and empathy, assessed through experimental tasks, and displayed emotional mental state inference and restraint as the bridge nodes between psychopathology and socio‐cognitive processes.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, ineffectiveness and interoceptive awareness were identified in the shortest pathway between emotional abuse and drive to thinness or bulimic symptoms in people with AN restricting type and with AN purging type or BN, respectively. In accordance with this study, early maladaptive schema (over‐vigilance and inhibition of emotions and impaired autonomy and performance) were external field nodes resulting highly central in samples with mixed EDs (Vervaet et al., 2020), although their possible bridge role was not assessed. Another study (Monteleone, Corsi, et al., 2020) explored the connections of ED‐specific and affective symptoms with mentalizing and empathy, assessed through experimental tasks, and displayed emotional mental state inference and restraint as the bridge nodes between psychopathology and socio‐cognitive processes.…”
Section: Resultssupporting
confidence: 81%
“…The high centrality of interpersonal difficulties has been highlighted also in other studies conducted in people with AN (Monteleone et al., 2019; Solmi et al., 2019) or in a mixed ED diagnostic group (Solmi et al., 2018). Furthermore, some studies identified also ineffectiveness feelings (Hilbert et al., 2020; Olatunji et al., 2018; Solmi et al., 2018; 2019; Vervaet et al., 2020), interoceptive awareness (Cascino et al., 2019; Olatunji et al., 2018; Solmi et al., 2018, 2019; Vervaet et al., 2020) or emotional regulation/internalising difficulties (Forrest et al., 2019; Levinson et al., 2017; Monteleone et al., 2019; Solmi et al., 2018, 2019; Vervaet et al., 2020) as central symptoms in ED networks. In most of these latter studies, drive to thinness as opposed to body dissatisfaction showed moderate‐high centrality and the Eating Disorder Inventory (EDI) instead of the EDE‐Q was employed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deve-se ressaltar que os possíveis mecanismos responsáveis pelo consumo calórico em animais não podem ser totalmente extrapolados para humanos adultos, que possuem outros fatores para desregular seu consumo calórico. Problemas de autoestima e inibição de emoções e sentimentos reduzem o consumo alimentar(VERVAET et al, 2020), enquanto que tristeza ou ansiedade estimulam seu aumento(BREWERTON et al, 2020).A maior concentração de HDL de PAE em relação a HAE pode ser apoiada estudo deJimenéz-Maldonado et al (2019), que observaram acúmulo hepático de colesterol gerado pela dieta hiperlipídica, o que inibe da expressão de ABC1 e reduz a produção de HDL. Além disso, o aumento da concentração sérica de triglicerídeos do subgrupo HAE em relação ao PAE e o aumento da quantidade de tecido adiposo do grupo H em relação ao P podem ser apoiados pelos achadosde Da Luz et al (2011), que observaram aumento da produção hepática de Lipoproteínas de Muito Baixa Densidade (VLDL) e do processo inflamatório no retículo endoplasmático (RE) causados pela dieta hiperlipídica, o que reduz a lipólise e a produção energética mitocondrial e aumenta o armazenamento de triglicerídeos no tecido adiposo.…”
unclassified